TERAPI PSIKOEDUKASI TERHADAP SELF-EFFICACY PADA PENDERITA TUBERCULOSIS PARU YANG SEDANG MENJALANI PENGOBATAN - Menajang, Indriany M.; Langelo, Wahyuny; Lumintang, Cyntia Theresia (Lasalle Health Journal, 2024)
Introduction: Pulmonary tuberculosis is an infectious disease that affects the physical and psychological health of sufferers. Psychoeducational therapy is providing information to patients to increase a person's understanding of the condition they have, so that sufferers can accept and be confident in undergoing treatment so that sufferers will have good self-efficacy. Objective: To determine whether there is an effect of psychoeducational therapy on self-efficacy in pulmonary tuberculosis sufferers who are undergoing treatment. Method: This research uses a quasi-experimental design with a One Group Pre and Post Test Design to see the effect of psychoeducational therapy on self-efficacy in pulmonary tuberculosis sufferers who are undergoing treatment. The sampling technique uses non-probability with a purposive sampling method. The population were pulmonary tuberculosis sufferers in the West Bitung Health Center Working Area with population of 38 respondents and sample size of 33 respondents suffering, used Federer formula. The statistical test used is the Wilcoxon sign test. Results: Before the pre-test self-efficacy was carried out, pulmonary tuberculosis sufferers had poor results after being given psychoeducational therapy and the post-test given showed good results. The results of bivariate data analysis show p-value 0.01 ≤ 0.05, so that Ho is rejected and Ha is accepted. Conclusions: There is an effect of psychoeducational therapy on self-efficacy in pulmonary tuberculosis sufferers who are undergoing treatment in the Working Area of the West Bitung Community Health Center.